In vivo production of novel vitamin D2 hydroxy-derivatives by human placentas, epidermal keratinocytes, Caco-2 colon cells and the adrenal gland - Slominski, A.; Kim, T.; Shehabi, Haleem; Tang, E.; Benson, Heather; Semak, I.; Lin, Z.; Yates, C.; Wang, J.; Li, W.; Tuckey, R. (Elsevier Ireland Ltd, 2014)
We investigated the metabolism of vitamin D2 to hydroxyvitamin D2 metabolites ((OH)D2) by human placentas ex-utero, adrenal glands ex-vivo and cultured human epidermal keratinocytes and colonic Caco-2 cells, and identified 20(OH)D2, 17,20(OH)2D2, 1,20(OH)2D2, 25(OH)D2 and 1,25(OH)2D2 as products. Inhibition of product formation by 22R-hydroxycholesterol indicated involvement of CYP11A1 in 20- and 17-hydroxylation of vitamin D2, while use of ketoconazole indicated involvement of CYP27B1 in 1α-hydroxylation of products. Studies with purified human CYP11A1 confirmed the ability of this enzyme to convert vitamin D2 to 20(OH)D2 and 17,20(OH)2D2. In placentas and Caco-2 cells, production of 20(OH)D2 was higher than 25(OH)D2 while in human keratinocytes the production of 20(OH)D2 and 25(OH)D2 were comparable. HaCaT keratinocytes showed high accumulation of 1,20(OH)2D2 relative to 20(OH)D2 indicating substantial CYP27B1 activity. This is the first in vivo evidence for a novel pathway of vitamin D2 metabolism initiated by CYP11A1 and modified by CYP27B1, with the product profile showing tissue- and cell-type specificity.